Reconstruction Of Good Corporate Governance In The Order To Realize Indonesia Incorporated As A Welfare Country (Regulatory-Deregulation-Reregulation Perspective Of The Jatimnomic Model) - Suparto Wijoyo; Prawitra Thalib; Mohamad Nur Kholiq (Universitas Airlangga, 2022)
The dynamic state administration reflects the crystallization of the idea that the presence of state governance called Good Corporate Governance (GCG) is a product of the development of the state's way of providing public services. The economic arrangement of the East Java model which can be called Jatimnomic in reconstructing GCG with the content of the corporate spirit. The purpose of this paper is to analyze the Good Corporate Governance (GCG) in order to realize Indonesia as a welfare state with the JATIMNOMIC model. The method used is a legal research type and uses a statute approach and a conceptual approach. The result of the discussion is that in realizing Good Corporate Governance (GCG) for People's Welfare, all state resources must be mixed in the formulation of national economic development policies that move in the wave of globalization with responsive leadership for a sustainable economy for the people's welfare. Reformative and solution construction of the national economy by making Indonesia a world economic supercorridor within the ASEAN (AEC) scope through the conception and implementation of what is called JATIMNOMIC.